33.2k views
4 votes
99 Points! Please help!!

Match each function with the corresponding function formula when h(x) = 2 – 2x and g(x) = –2^x + 2.


k(x) = (h – g)(x)

k(x) = (g + h)(x)

k(x) = (h – 2g)(x)

k(x) = (2g + h)(x)

k(x) = (2h – 2g)(x)

k(x) = (g – h)(x)





k(x) = 6 - 2 ^x+1 - 2x

k(x) = 2x - 2^x

k(x) = 2^x+1 - 2x - 2

k(x) = 4 - 2^x - 2x

k(x) = 2^x - 2x

k(x) = 2^x+1 - 4x

User Jason OOO
by
5.2k points

2 Answers

2 votes

funtions: a, b, c...

formulas: 1, 2, 3...

A and 5, F and 2, B and 4, D and 1, C and 3, E and 6

User Gishu
by
5.0k points
3 votes

k(x) = (h – g)(x) k(x) = 2x - 2^x

k(x) = (g + h)(x) k(x) = 4 - 2^x - 2x

k(x) = (h – 2g)(x) k(x) = 2^x+1 - 2x - 2

k(x) = (2g + h)(x) k(x) = 6 - 2 ^x+1 - 2x

k(x) = (2h – 2g)(x) k(x) = 2^x+1 - 4x

k(x) = (g – h)(x) k(x) = 2x - 2^x

User Wilfrido
by
5.9k points